Microwave-Assisted Synthesis of Benzyl Benzotriazoles - YUYE, YU (Asian Journal of Chemistry, 2010)
A series of substituted benzotriazoles were synthesized by substituted benzyl chloride in the presence of benzotriazole under the condition of microwave irradiation.